Gastroretentive Drug Delivery System of Amoxycillin: Formulation and In Vitro Evaluation - VINAY PANDIT; SARASIJA SURESH; HEMANTH JOSHI (International Journal of Pharma and Bio Sciences, 2010)
Gastro retentive drug delivery systems of Amoxycillin trihydrate as floating tablets were prepared with the objective to obtain site-specific drug delivery and to extend its duration of action. More over the floating system of amoxicillin will provide increased local and systemic action in stomach. The formulations were prepared as matrix tablets in the form non effervescent tablets. Various grades of hydroxy propyl methyl cellulose (HPMC) were used to achieve controlled release of the drug. The drug and polymers were found to be compatible as seen by IR studies. Initially granules were prepared by wet granulation technique and compressed into tablets. The prepared tablets were evaluated for weight variation, hardness, friability, drug content, buoyancy and in-vitro dissolution studies. Optimized formulation of amoxicillin was found to have increased gastric residence prolonging the release of drug with 85% of drug release in 6 hours by diffusion. The mechanism of drug release was found to be diffusion and followed combination of zero order and first order kinetics. Hence gastro retentive drug delivery system of Amoxycillin trihydrate is a promising approach as it can lead to decrease in the frequency of administration and ultimately lead to better patient compliance.